The genetic makings of South Asia. (December 2018) - Metspalu, Mait; Mondal, Mayukh; Chaubey, Gyaneshwer
Abstract : South Asia is home for more than a billion people culturally structured into innumerable groups practicing different levels of endogamy. Linguistically South Asia is broadly characterized by four major language families which has served as access way for disentangling the genetic makings of South Asia. In this review we shall give brief account on the recent developments in the field. Advances are made in two fronts simultaneously. Whole genome characterisation of many extant South Asians paint the picture of the genetic diversity and its implications to health-care. On the other hand ancient DNA studies, which are finally reaching South Asia, provide new incites to the demographic history of the subcontinent. Before the spread of agriculture, South Asia was likely inhabited by hunter-gatherer groups deriving much of their ancestry from a population that split from the rest of humanity soon after expanding from Africa. Early Iranian agriculturalists mixing with these local hunter-gatherers probably formed the population that flourished during the blossoming of the Indus Valley Civilisation. Further admixture with the still persisting HG groups and population(s) from the Eurasian Steppe, formed the two ancestral populations (ANI and ASI), the north-south mixing pattern of whom is known today as the 'Indian Cline'. Studies on natural selection in South Asia have so far revealed strong signals of sweeps that are shared with West Eurasians. Future studies will have to fully unlock the aDNA promise for South Asia.